2003
DOI: 10.1002/adma.200305393
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Pentacene Active Layer Organic Thin‐Film Transistors

Abstract: Organic thin-film transistors (OTFTs) have potential for use in many low-cost, large-area electronic applications such as smart cards, radio-frequency (RF) identification tags, and flatpanel displays. To date, OTFTs with the best overall reported performance have been based on the organic semiconductor pentacene, with carrier field-effect mobility > 2 cm 2 V ±1 s ±1 .[1]Molecular ordering is believed to play a large role in the performance of devices based on organic active layer materials, [2,3] especially fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
252
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(263 citation statements)
references
References 8 publications
8
252
0
3
Order By: Relevance
“…For TIPS-pentacene however, the face-to-face stacking shown in Fig. 4(b) indicates a significantly more anisotropic environment, 41,44 and a greater influence of intermolecular interactions between neighbouring molecules 42,44 (also pointed to by the significant difference between solution and film absorption spectra. 31 ) We note that anisotropy has been shown to play an important role in triplet exciton diffusion in molecular semiconductors, with the experimental characterization typically relying on radiative triplet-triplet annihilation to track energy migration.…”
Section: Discussionmentioning
confidence: 99%
“…For TIPS-pentacene however, the face-to-face stacking shown in Fig. 4(b) indicates a significantly more anisotropic environment, 41,44 and a greater influence of intermolecular interactions between neighbouring molecules 42,44 (also pointed to by the significant difference between solution and film absorption spectra. 31 ) We note that anisotropy has been shown to play an important role in triplet exciton diffusion in molecular semiconductors, with the experimental characterization typically relying on radiative triplet-triplet annihilation to track energy migration.…”
Section: Discussionmentioning
confidence: 99%
“…Amorphous films of 6,13-bis(triisopropylsilylethynyl)pentacene (TIPSpentacene), 47 PCBM, PC 71 BM, and T1 were prepared by spin-casting the materials from chloroform or chlorobenzene solutions, and crystallinity was induced by thermal annealing. Amorphous films of rubrene were prepared by evaporating at a fast rate, and crystallinity was similarly induced by annealing.…”
Section: Film Morphology and Photobleach Ratementioning
confidence: 99%
“…[54][55][56][57] Minari et al examined the effects of intermolecular distance and π orbital overlap in a series of metal-substituted octaethylporphyrin OFETs with the molecules arranged face-to-face along the c axis, and found µ FE to be inversely dependent on the intermolecular spacing. 58 XRD measurements on MTBP thin-films have shown that molecules stack in the herringbone arrangement along the b axis, with the molecule face parallel to (114) and the HOMO orbital surface parallel to the molecule face.…”
Section: Discussionmentioning
confidence: 99%